2021
DOI: 10.3390/min11101136
|View full text |Cite
|
Sign up to set email alerts
|

Historical Outline of Iron Mining and Production in the Area of Present-Day Poland

Abstract: The article presents the history of iron ore mining and production in present-day Poland and takes into account mining and production techniques and the influence of mining on the development of the surrounding areas. Examples of development are presented for the most important iron ore mining centers established since the period of the so-called Roman influences—Lower Silesia in the region of Tarchalice and the Świętokrzyskie region in the area of Góry Świętokrzyskie (Świętokrzyskie Mountains). The oldest tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The analysis of charcoal found in the slag gave the date of 196 BC-4 AD, falling within the range of isotope analyses conducted so far, i.e., 300 BC-200 AD [21]. This confirms that the analyzed slags were formed during the Roman influence period, which was characterized by increased metallurgical activity in the areas of present-day Poland [21,[40][41][42]. Apart from the Holy Cross Mountains, there were many smaller metallurgical centers in Poland.…”
Section: Agesupporting
confidence: 68%
See 1 more Smart Citation
“…The analysis of charcoal found in the slag gave the date of 196 BC-4 AD, falling within the range of isotope analyses conducted so far, i.e., 300 BC-200 AD [21]. This confirms that the analyzed slags were formed during the Roman influence period, which was characterized by increased metallurgical activity in the areas of present-day Poland [21,[40][41][42]. Apart from the Holy Cross Mountains, there were many smaller metallurgical centers in Poland.…”
Section: Agesupporting
confidence: 68%
“…Isotope analyses show that iron smelting in Masovia was carried out in the period covering at least 2450-1890 BP [41], with the greatest development occurring in the first two centuries AD [40]. In Lower Silesia (Poland), the first traces of metallurgical activity date back to the third-first century BC [42]. Dating of iron objects from Nowe Brzesko (Lesser Poland Voivodeship) gave an age in the range of 217-412 AD [37].…”
Section: Agementioning
confidence: 99%
“…In the early Middle Ages, written sources confirm that in the Alpine areas close to Valtellina, Valcamonica (in the Brescia area), Valseriana and Valle Scalve (in the Bergamo area), iron mining and metallurgy were already organised and operational to extract and process raw ore. In the area of Bienno in Valcamonica, the excavation of the site of Ponte Val Gabbia III has shown that workers capable of voluntarily decarburising pig iron existed as early as the 5th-6th century, providing a fundamental impulse to the technological perfection of iron metallurgy [16][17][18]. While the transition from the direct to the indirect method represented a decisive technical innovation for the development of the iron and steel industry, it was not until the 13th century that important economic, political, administrative and legislative implications arose.…”
Section: History and Archaeology Of Iron In The Alpine Areasmentioning
confidence: 99%